1989
DOI: 10.1002/eji.1830190313
|View full text |Cite
|
Sign up to set email alerts
|

Terminal deoxynucleotidyl transferase‐positive B cell precursors in fetal lymph nodes and extrahemopoietic tissues

Abstract: Terminal deoxynucleotidyl transferase (TdT)-positive B cell precursors populate fetal lymph nodes (LN) of mid-term (16th-22th week) fetuses. These cells have a B cell phenotype (HLA-DR, CD45R, CD22, mu) and lack mature differentiation antigens (CD1c, CD20, L26). TdT+ cells are also present in the extranodal mesenteric mesenchyme, pancreas and LN primordia. Extranodal TdT+ cells are found among proliferating (i.e. Ki-67+) B cells and lack leukocyte function-associated antigen (LFA-1) and HLA-DQ; these latter mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…15 and Fig. 2), suggesting the presence of immature B cells in peripheral lymphoid organs where they are localized outside the GC microenvironment (42)(43)(44). Taken together, our results and these observations indicate that the CD77 marker does not identify the two histologically defined populations of GC B cells.…”
Section: Discussionmentioning
confidence: 70%
“…15 and Fig. 2), suggesting the presence of immature B cells in peripheral lymphoid organs where they are localized outside the GC microenvironment (42)(43)(44). Taken together, our results and these observations indicate that the CD77 marker does not identify the two histologically defined populations of GC B cells.…”
Section: Discussionmentioning
confidence: 70%
“…This conclusion is supported by a previous study reporting the presence of TdT ϩ immature B cells but not T cells in fetal lymph nodes and spleens. 19 However, since the majority of RAG ϩ /TdT ϩ cells did not express lineage-specific markers and since RAG expression in peripheral T-cells has been reported, 20,21 this question requires further examination.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by a previous study reporting the presence of TdT ϩ immature B cells but not T cells in fetal lymph nodes and spleens. 19 However, since the majority of RAG ϩ /TdT ϩ cells did not express lineage-specific markers and since RAG expression in peripheral T-cells has been reported, 20,21 this question requires further examination.The second important observation regards the distribution of RAG ϩ /TdT ϩ cells ( Figure 5). Several recent studies have suggested that expression of the RAGs and other components of the V(D)J recombination machinery may be reinduced in peripheral mature B cells in the context of germinal center reactions, and it has been proposed that this mechanism may rescue B cells producing low avidity antibodies.…”
mentioning
confidence: 99%
“…B cell lymphopoiesis in embryos starts around coelomic cavities: terminal deoxynucleotidyltransferase-positive B cell precursors have been detected in early human fetal mesentery (1), and RAG-1 gene expression in mouse embryos begins in the paraaortic splanchnopleura on day 9 of gestation, 3 days before it starts in the liver (2). Later into gestation, the main site of B cell lymphopoiesis is the liver.…”
mentioning
confidence: 99%